Strategi Belajar Bahasa Inggris Pada Era Revolusi Digital 4.0 di Komunitas Duta Bahasa Provinsi Bangka Belitung - Eka Dyah Puspita Sari; Ummi Nurjamil Baiti Lapiana; Memet Sudaryanto (Politeknik Negeri Cilacap, 2022)
Language is one of the crucial components to face industrial revolution 4.0. Mastery in English, as a foreign language, can be beneficial for people. It can give us chance to explain information, to tell the fact, and to express ideas in various communities in the world. Some ways can be implemented in autonomous learning in digital era 4.0. They are extensive reading and improving writing skills. Extensive reading is an approach to learning English by implementing much time to read books in a short time. The second way is improving writing skills. The role of improving writing skills is to boost academic and career achievements. When someone improves his academic and career, he automatically improves his self-esteem in communicating and interacting with others in English.